2006
DOI: 10.1111/j.1471-4159.2006.03972.x
|View full text |Cite
|
Sign up to set email alerts
|

Calsenilin interacts with transcriptional co‐repressor C‐terminal binding protein(s)

Abstract: Calsenilin/potassium channel-interacting protein (KChIP)3/ downstream regulatory element sequence antagonist modulator (DREAM) is a neuronal calcium-binding protein that has been shown to have multiple functions in the cell, including the regulation of presenilin processing, repression of transcription and modulation of A-type potassium channels. To gain a better understanding of the precise role of calsenilin in specific cellular compartments, an interactor hunt for proteins that bind to the N-terminal domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Especially KChIP3, but also KChIP1, KChIP2 and KChIP4, may fulfill the function of a transcriptional repressor, either directly, by binding to downstream regulatory element (DRE) sites of genes [19,5561], or indirectly, by binding to other transcription factors [6264]. Here the focus is put on direct KChIP-mediated control of gene transcription (Figure 1C), which appears to be commonly linked to excitability.…”
Section: Kchips Control Gene Transcriptionmentioning
confidence: 99%
“…Especially KChIP3, but also KChIP1, KChIP2 and KChIP4, may fulfill the function of a transcriptional repressor, either directly, by binding to downstream regulatory element (DRE) sites of genes [19,5561], or indirectly, by binding to other transcription factors [6264]. Here the focus is put on direct KChIP-mediated control of gene transcription (Figure 1C), which appears to be commonly linked to excitability.…”
Section: Kchips Control Gene Transcriptionmentioning
confidence: 99%
“…It was further discovered that binding of calcium to these EF regions resulted in a change in configuration that impairs interaction of the DREAM molecule with DNA (Osawa et al, 2001). Recent studies utilizing yeast two-hybrid screening reveals that DREAM also has the capacity to interact with a number of proteins in different cellular compartments (Savignac et al, 2005;Zaidi et al, 2006). Our demonstration that DREAM is expressed in GT1-7 cells and that it is a part of the OCT1BS-a binding complex supports its involvement in the process of NSE-related GnRH promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that in addition to direct binding to DNA through downstream regulatory elements (DRE), DREAM can also interact and modulate the action of transcriptional factors through protein-protein interaction (Ledo et al, 2002;Rivas et al, 2004;Zaidi et al, 2006). In the NSE region of the GnRH promoter, there are no sequences that offer a high degree of homology to consensus DRE sequence.…”
Section: Emsa Analysis Of Dream Binding To the Oct1bs-a Sitementioning
confidence: 99%
“…Interestingly, although the binding is insensitive to Ca 2+ , regulation of the gating needs the integrity of the EF-hands in the DREAM protein [3]. In another yeast two-hybrid assay, using the N-terminal of DREAM as bait the interactions with the transcriptional corepressor C-terminal binding protein 2 (CtBP2) and its homolog CtBP1 were identified [16]. Interestingly, histone deacetylase (HDAC) protein and activity was found to be associated with the DREAM-CtBP immunocomplex, sug- gesting a mechanism by which DREAM-CtBP may act to repress transcription.…”
Section: Defining the Dream Interactomementioning
confidence: 99%
“…For instance, DRE sites contribute to basal and induced expression of a number of immediate early transcription factors including c-fos, c-jun and ICER [2,4]. In addition to its regulation by calcium, binding of DREAM to DNA is hampered by its interaction with phosphoCREM [14], while interaction with other transcription factors like CREB, TTF-1 or CtBP2 allows DREAM to regulate transcription of genes that do not contain DRE sites ( Figure 2) [7,15,16]. Outside the nucleus, DREAM regulates many cellular functions through selective interactions with an increasing number of proteins that constitute the DREAM interactome and underscore DREAM multifunctional properties.…”
Section: Dream a Multifunctional Proteinmentioning
confidence: 99%